Effects of negative triangularity shaping on energetic particle driven Alfvén eigenmodes in DIII-D*Notice: This manuscript has been authored by UT-Battelle, LLC, under Contract DE-AC05-00OR22725 with the US Department of Energy (DOE). The US government retains and the publisher, by accepting the article for publication, acknowledges that the US government retains a nonexclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for US government purposes. DOE will provide public access to these results of federally sponsored research in accordance with the DOE Public Access Plan (http://energy.gov/downloads/doe-public-access-plan). (26th October 2021) - Ghai, Y.; Spong, D.A.; Varela, J.; Garcia, L.; Van Zeeland, M.A.; Austin, M.E.
Abstract: Shape variations from positive to negative triangularity may lead to improved performance regimes in a tokamak with a reduction in microturbulence as well as improved thermal confinement. The motivation of this investigation is to model and compare the neutral beam driven Alfvén eigenmode (AE) activity in two DIII-D discharges with positive and negative triangularity shaping of plasma. The simulations are performed using the linear version of the FAR3d code, which solves the reduced MHD equations for thermal plasma with addition of moment equations for the energetic ion density and parallel velocity with appropriate Landau closure relations. Our numerical results indicate that for similar physical parameters, the unstable AEs observed in the negative triangularity case have lower growth rates as compared to the positive triangularity regime. Our findings may be useful to analyze the influence of the reverse-D like geometry on the AE instabilities in DIII-D and may lead to better configurations for minimizing fast ion losses in a tokamak device.